Importance of memories about soviet deportation in Lithuanian autobiography - Šutinienė, Irena (Genocidas ir rezistencija, 2008)
This presentation analyses the autobiographical accounts of people who experienced repression from the latter perspective in order to reveal the subjective meanings of these events for the participants. The analysis focuses on 16 autobiographies told and written in five Lithuanian towns and their surroundings (Antalieptė, Griškabūdis, Panemunėlis, Papilė and Rumšiškės) between 2001 and 2005. They do not represent all the possible meanings of repression for their authors, let alone for all the repressed, but their commonalities in content and structure help to reveal some typical contemporary meanings of the experience of repression, which are likely to be common to the memory of many people with similar fates, and which provide the structure for the collective memory of these events.